-6p-27=5(2p+1)

Simple and best practice solution for -6p-27=5(2p+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6p-27=5(2p+1) equation:



-6p-27=5(2p+1)
We move all terms to the left:
-6p-27-(5(2p+1))=0
We calculate terms in parentheses: -(5(2p+1)), so:
5(2p+1)
We multiply parentheses
10p+5
Back to the equation:
-(10p+5)
We get rid of parentheses
-6p-10p-5-27=0
We add all the numbers together, and all the variables
-16p-32=0
We move all terms containing p to the left, all other terms to the right
-16p=32
p=32/-16
p=-2

See similar equations:

| 1/3(9n+12)=19 | | 0=-4.9t^2+3t | | 1/9p-5/18=-1/6p+1/3 | | 120+0.20x=30+0.50x | | 17=2L+2W,l*W=15 | | 30+3x=2(1+5x) | | 3n+42=3∙5+7∙6 | | -8/9(3t+5)=2/3-12 | | (7x+3)/(5x-4)=3/2 | | 154=6x-2(-3x-5) | | 5y+3/7=3/7 | | 5*x+24=5(x-1.5) | | (w^2/8)-(w/2)-4=0 | | N=1.76t^2-13.32t+41 | | 5*x+24=5(x-1/2) | | 4x^2+56x/3-80=0 | | 84+76+77+75+2x/6=80 | | 25/6=-x+1/2-8/3x | | 4x^2+56/3*x-80=0 | | x+2/3=13/9;{5/9,2/3,7/9} | | +2y-8=3(y-11) | | 200=1.5x | | X+2x+1+2x+3=29 | | (m-2)=-2(-2m+6) | | (3+4x)=16 | | x/2+x=3 | | (m-2)=-2(-2m+6 | | 3(x5)=2(x+5) | | X2+4x=20 | | 3(x5)=2(x+50 | | 14+1/3x=180 | | 7/4w-1=20 |

Equations solver categories